Use of ECT in Nepal: A One Year Study From the Country’s Largest Psychiatric Facility - Subedi, Sandip (J Clin Diagn Res, 2016)
INTRODUCTION: Electro-Convulsive Therapy (ECT) refers to the electrical stimulation of the brain to produce seizures for therapeutic purpose. Since the development of ECT, it’s use has been consistent. Inspite of the common use, data pertaining to the use of ECT in Nepal is lacking. AIM: This study was undertaken with the aim of exploring the clinico-demographic profile of patients treated with ECT in the largest psychiatry facility in the country. MATERIALS AND METHODS: It is a retrospective descriptive study of patients who were treated with ECT after admission in the inpatient psychiatry unit of Universal College of Medical Sciences Teaching Hospital, Bhairahawa, Nepal during a period of one year (August 2012 to July 2013). RESULTS: Out of 1095 patients admitted during the specified period, 81 (7.39%) patients received ECT. About 44.44% of the patients belonged to 20-29 years age group. Female patients constituted more than half of the subjects (55.56%). Review of diagnostic profile showed that majority of patients receiving ECT were suffering from Schizophrenia (44.4%), followed by Bipolar Affective Disorder/Mania (29.6%), Depressive disorder (11.1%), Acute and Transient Psychotic Disorder (6.2%), Post-partum Psychosis (3.7%) and substance induced mood/psychotic disorders (3.7%). A significant majority of subjects (75.3%) received about 5-7 ECT treatments. The mean seizure duration after ECT treatment was 31.13±5.79 seconds. No any major complications were noted during ECT treatment. CONCLUSION: This study suggests that ECT, use, as a treatment modality is common in young adults and females with Schizophrenia being the most common indication. Direct ECT is safe when used judiciously.